FirstLight III: rest-frame UV-optical spectral energy distributions of simulated galaxies at cosmic dawn - Ceverino, Daniel; Klessen, Ralf S.; Glover, Simon (Arxiv, 2019)
Using the FirstLight database of 300 zoom-in cosmological simulations we provide rest-frame UV-optical spectral energy distributions of galaxies with complex star-formation histories that are coupled to the non-uniform gas accretion history of galactic halos during cosmic dawn. The population at any redshift is very diverse ranging from starbursts to quiescent galaxies even at a fixed stellar mass. This drives a redshift-dependent relation between UV luminosity and stellar mass with a large scatter, driven by the specific star formation rate. The UV slope and the production efficiency of Lyman continuum photons have high values, consistent with dust-corrected observations. This indicates young stellar populations with low metallicities. The FirstLight simulations make predictions on the rest-frame UV-optical absolute magnitudes, colors and optical emission lines of galaxies at z=6-12 that will be observed for the first time with JWST and the next generation of telescopes in the coming decade.